: بلاد يوربا النجيرية أنموذجا : تتطبيق ّ الميراث الشرعي بدلا من نطام الميراث العرفي - Shittu Bilal Yusuf; Nik Rahim Nik Wajis; Alawiye Abdul Mumin Abdur Razzaq; Irwan Mohd Subri (Universiti Sains Islam Malaysia, 2024)
MJSL 2018-dec